Meaning the Values of Onang-Onang Voice at the Manortor's Tradition - Yusni Khairul Amri; Dian Marisha Putri (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The margondang ceremony is completed with panaekkon gondang to open the galanggang 'na so marongit, tapian na so marlinta' which is followed by a manortor ceremony accompanied by onang-onang poetry. Poems sung by paronang-onang accompanied by gondang instrumental music at traditional ceremonies. The data of onang-onang poetry was taken at the Angkola traditional marriage ceremony, in the city of Medan. Barthes (1957:140-142) uses the concept of value according to Barthes (1957:140-142), namely: 1) values related to the subject; 2) values appear in a practical context; 3) value concerns the properties that are 'added' by the subject. taken based on the analysis data classified the results of the analysis of the values of the Angkola traditional onang-onang poetry, among others: the values contained in the lyrics of the Angkola traditional onang-onang poems include: 1. Values Relating to the Subject: a) The Value of Parental Love for Children and Son-in-law b) Advice for Living in harmony, c) Maintaining kinship relations. 2. Values appear in a practical context: a) Belief in the Almighty, b) Forms of Parental Love. 3. The Value of the Characteristics 'Added' by the Subject: a) Angkola Identity Value, and b) Aesthetic Value